Analisis Gangguan Tidak Seimbang pada Line Transmisi GI Sungguminasa-GI Tallasa - Marwan, Marwan; L, Ruslan; Samsul, Nur Malasari (INTEK: Jurnal Penelitian, 2016)
The main purpose of this research is to determine the short circuit current when there is a fault occurred on Transmission line between Sungguminasa Sub Station and Tallasa Sub Station. PT. PLN measured that the short circuit current on this transmission line is 2.8 kA. To justify the result, symmetrical component method is applied using MATLAB. The results shows that measured value from PLN is equal with the obtained results using MATLAB. This research was conducted on 19th January 2016 at 14:13 WITA.